Hygiene and disinfection measures for monkeypox virus infections - Eggers, Maren; Exner, Martin; Gebel, Jürgen; Ilschner, Carola; Rabenau, Holger F.; Schwebke, Ingeborg (GMS Hygiene and Infection Control, 2022)
In Germany, recommendations on infection prevention and control of current virus outbreaks are given as communications by the Association for Applied Hygiene e.V. (VAH) together with the joint Disinfectant Commission of the German Association for the Control of Virus Diseases e.V. (DVV) and the Society of Virology* (GfV). The DVV was founded in 1954 in response to the ongoing threat to the population from polio and was given its current name in 1977. The DVV is supported by the Federal Ministry of Health, the Ministries of Health of the Federal States, scientific societies, as well as social foundations and organisations. Private individuals cannot be members of the DVV. The Society of Virology e.V. (GfV) is a scientific society for all virological fields in Germany, Austria and Switzerland, and is thus the largest virological society in Europe. With numerous commissions, guidelines and statements, it is the authoritative contact for research, healthcare and politics. The joint commission “Virus Disinfection” of these scientific societies focuses on the efficacy of chemical disinfection procedures against viruses. The VAH bundles the expertise of scientific societies and experts on infection prevention and is particularly committed to the quality assurance of hygiene measures. With the VAH disinfectant list, the association provides the standard reference for the selection of high-quality disinfection procedures. This disinfectant list has a tradition of more than 60 years in Germany.The original German version of this document was published in August 2022 and has now been made available to the international professional public in English. The document contains recommendations on hygiene and disinfection measures for monkeypox virus infections. Disinfectants against monkeypox must have at least proven efficacy against enveloped viruses (active against enveloped viruses); products with the efficacy ranges “limited virucidal activity” and “virucidal” can also be used. The disinfectant list of the VAH or the disinfectant list of the Robert Koch Institute are available for the selection of products. Especially in the case of contamination with crust or scab material, it should be noted that protein contamination can have a protective or stabilising effect on monkeypox. Therefore, cleaning – before disinfection – should always be carried out in this situation. Preventive measures such as vaccination and hygiene in the vicinity of people with monkeypox must be taken to prevent transmission to small children, pregnant women or people with a pronounced immune deficiency.